(untitled) (Texas Journal of Medical Science, 2023)
Diabetic foot syndrome, which is one of the complications of diabetes mellitus, is characterized by a change in biochemical parameters from negative to positive, and thanks to a new method in Uzbekistan for the treatment of diabetic foot syndrome, patients recover their working capacity and resume their quality of life. Study of the effect of the new drug "Rheomannisol" on vital organs, taking into account of diagnostics and prevention of pathophysiological aspects in the complex treatment of experimental diabetic foot syndrome.